A Combined In Vitro/In Silico Approach to Identifying Off-Target Receptor Toxicity - Leedale, Joseph; Sharkey, Kieran J.; Colley, Helen E.; Norton, Áine M.; Peeney, David; Mason, Chantelle L.; Sathish, Jean G.; Murdoch, Craig; Sharma, Parveen; Webb, Steven D. (iScience, 2018)
Many xenobiotics can bind to off-target receptors and cause toxicity via the dysregulation of downstream transcription factors. Identification of subsequent off-target toxicity in these chemicals has often required extensive chemical testing in animal models. An alternative, integrated in vitro/in silico approach for predicting toxic off-target functional responses is presented to refine in vitro receptor identification and reduce the burden on in vivo testing. As part of the methodology, mathematical modeling is used to mechanistically describe processes that regulate transcriptional activity following receptor-ligand binding informed by transcription factor signaling assays. Critical reactions in the signaling cascade are identified to highlight potential perturbation points in the biochemical network that can guide and optimize additional in vitro testing. A physiologically based pharmacokinetic model provides information on the timing and localization of different levels of receptor activation informing whole-body toxic potential resulting from off-target binding. [Display omitted] •Development of in vitro/in silico framework for identifying off-target toxicity•Mathematical modeling of receptor signaling and related transcriptional activity•Identification of key events in the signaling pathway•Off-target receptor activation in vivo simulated using PBPK modeling Toxicology; Computational Toxicology; Systems Biology